2003
DOI: 10.1063/1.1618375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ca content on the electronic structure of Pb1−xCaxTiO3 perovskites

Abstract: This study performs O K-and Ti L 3,2-edge x-ray absorption near-edge structure ͑XANES͒ measurements and first-principles pseudopotential calculations for the electronic structures of ABO 3-type Pb 1Ϫx Ca x TiO 3 (xϭ0-1) perovskites. The features in the O K-edge XANES spectra are found to be contributed primarily by hybridization between O 2p and Ti 3d, Pb 6p, and Ca 3d orbitals. The O K-edge XANES spectra reveal that partial substitution of A cations, Pb, by Ca not only decreases O 2p-Pb 6p but also O 2p-Ti 3d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 16 publications
(15 reference statements)
5
36
0
Order By: Relevance
“…12 These authors observed that this splitting disappeared in the samples containing high concentrations of Ca and suggested a restoration of the Ti ion to the center of the octahedron. Thus, they correlated the changes observed in the L 3 e g peak to the structural changes in the first oxygen atoms around titanium atoms.…”
Section: A Ti L 32 Xanes Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…12 These authors observed that this splitting disappeared in the samples containing high concentrations of Ca and suggested a restoration of the Ti ion to the center of the octahedron. Thus, they correlated the changes observed in the L 3 e g peak to the structural changes in the first oxygen atoms around titanium atoms.…”
Section: A Ti L 32 Xanes Resultsmentioning
confidence: 99%
“…18 The separation between the L 3 and L 2 edges is attributed to Ti 2p 3/2 ͑L 3 ͒ and 2p 1/2 ͑L 2 ͒ spin orbit splitting, which is around 5.3 eV and is comparable to that observed in TiO 2 and other mixed perovskite compounds. [8][9][10][11][12][13][14] The crystal field at both the L 3 and L 2 edges splits the 3d band into t 2g and e g subbands. 21 The split observed at the D peak, shown in greater detail in Fig.…”
Section: A Ti L 32 Xanes Resultsmentioning
confidence: 99%
See 3 more Smart Citations